Two-Year Integrated Efficacy And Safety Analysis Of Benralizumab In Severe Asthma - FitzGerald, J Mark (J Asthma Allergy, 2019)
BACKGROUND: Benralizumab is an interleukin-5 receptor alpha–directed cytolytic monoclonal antibody. Treatment with benralizumab significantly reduces exacerbations and improves lung function after 1 year for patients with severe, uncontrolled eosinophilic asthma. OBJECTIVE: We explored whether benralizumab efficacy was sustained after an additional year of treatment while maintaining an acceptable safety profile. METHODS: Data from the pivotal 48-week SIROCCO and 56-week CALIMA studies were integrated with data from the predefined 56-week adult phase of the BORA extension study to provide a 2-year integrated efficacy and safety analysis of benralizumab. BORA enrolled patients who had completed SIROCCO or CALIMA. Patients receiving benralizumab 30 mg subcutaneously, either every 4 weeks (Q4W) or every 8 weeks (Q8W; first three doses Q4W), were assessed. Efficacy was evaluated based on baseline blood eosinophil counts from the pivotal studies (≥300 and <300 cells/μL). RESULTS: Mean treatment exposures were 24.3 (Q4W, n=518) and 24.6 (Q8W, n=512) months. Exacerbation frequency reductions observed in SIROCCO/CALIMA were maintained; 50% of the patients had no exacerbations during the 2-year study period (crude exacerbation rate, Q8W: 0.56 exacerbations/year for patients with blood eosinophil counts ≥300 cells/μL). Lung function improvements with benralizumab were maintained for 2 years, as represented by increases in mean prebronchodilator forced expiratory volume in 1 second from baseline of 0.343 L and 0.364 L with 1 and 2 years of benralizumab Q8W treatment, respectively, for patients with blood eosinophil counts ≥300 cells/μL. Health-related quality of life improvements with benralizumab observed in the pivotal studies were also sustained. Adverse events and serious adverse event rates were similar between the BORA extension and SIROCCO/CALIMA periods, with no new or unexpected occurrence of adverse events. CONCLUSION: This benralizumab 2-year integrated analysis further supports long-term use of benralizumab for patients with severe, uncontrolled eosinophilic asthma.